Implementation of Fintech (QRIS) as an Effort to Increase Digital Payment Transactions among MSMEs - Revita Sari; Muhsin Lambok Ilvira (Golden Ratio of Data in Summary, 2026)
Transactions that were initially solely conducted in cash are now easier through the development of Financial Technology (Fintech), examples of which include Go-pay, OVO, Shopee pay, and the Quick Response Code Indonesian Standard (QRIS). The Quick Response Code Indonesian Standard (QRIS) can be an alternative to improve payment efficiency for MSMEs. QRIS (Quick Response Code Indonesian Standard) Merchant is a digital payment solution designed to facilitate transactions between customers and businesses. In the context of MSMEs (Micro, Small, and Medium Enterprises), QRIS Merchant plays a crucial role in supporting business growth and development. The research problem is how to implement QRIS among MSMEs around the Muhammadiyah University of North Sumatra (UMSU). Other objectives are to identify obstacles faced, understand the perceived benefits, and find solutions to problems in implementing QRIS. The optimization of QRIS use is analyzed through interviews and direct observation of merchants who have used QRIS and from the perspective of consumers who have transacted using the system.